The Effectiveness of Al-MuhÄdastah Textbook to Improve Arabic Speaking Skills - Mahmudi, Ihwan; Maha, Marheni Br; Lubis, Zulfahmi; Silmy, Ahmad Nahidl; Zalzuli, Ahmad (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This research aimed to develop a textbook called "al-Muhadastah" and tested its effectiveness in improving Arabic language skills for all first-year students at the Mawaridussalaam Islamic Boarding School during the 2021-2022 academic years. This research was triggered by a phenomenon that according to new students learning Arabic, muhadastah lessons were difficult and boring. This was because the textbook used was not in accordance with their abilities. The research method employed the ADDIE Research and Development (R&D) concept. The design of this research was One-Group Pre-test and Post-test Design. Interviews, questionnaires, tests, and papers were employed to obtain the data. This study's results were based on the presentation and analysis of data on the effectiveness of the textbook â€œal-Muhadastah al-Yaumiyyahâ€ to improve the Arabic speaking skills of the new students at Mawaridussalam Islamic Boarding School. The textbooks developed had also been declared valid by experts, comprising the experts of language, design, and content. Pre-test and post-test results showed that before using the textbooks students had a mean score of (59.17) on post-tests. After using the textbooks, that score went up to (80.50) which meant that the pre-test and post-test mean scores of the students differed significantly. Similarly, the results of the efficiency test (Paired Sample T-Test) were efficient. The results obtained from these two experiments by analysing the data from the second experiment showed a significant difference between the two experiments that Sig. (2-tailed) the result was 0,000 < (less than) 0,005. It was found that the medium might help students get better at speaking Arabic and understand the subject better.